Association between hair cortisol concentration and behavioral difficulties in children and adolescents. (August 2022) - Jahns, Cora Charlotte; Poulain, Tanja; Vogel, Mandy; Kiess, Wieland
Abstract: This study aimed to assess associations between behavioral difficulties and an objectively measurable indicator for long-term stress (hair cortisol) in children and adolescents. We expected increased hair cortisol levels in participants with more externalizing (conduct problems, hyperactivity/inattention) or internalizing (peer relationship problems, emotional problems) behavioral difficulties. Behavioral difficulties were assessed using the parent version of the Strengths and Difficulties Questionnaire (SDQ). Hair cortisol concentration (HCC), measured via liquid chromatography mass spectrometry (LC-MS3), was used as stress marker. A 1 cm strand of hair was cut off from the occipital or parietal cranium closest to the scalp. The study sample comprised 1321 children and adolescents aged between 3 and 17 years participating in the LIFE Child cohort study (Leipzig, Germany). To assess associations, we applied multiple linear regression analyses. Only a few associations met expectations, others contradicted our hypotheses. No association reached statistical significance. The present findings may suggest that behavioral difficulties gathered by SDQ are not associated with stress measured through HCC. Highlights: No significant association between HCC and behavioral difficulties in children and adolescents. SDQ subscales might not be associated with the stress measured through HCC levels. Inconsistent patterns of (non-significant) associations depending on age and gender.